Gender Disparity and Reasons behind Elderly Relocation to Old-age Homes - A Narrative Review - Sahaja Nagisetty (Journal of the Indian Academy of Geriatrics)
Aging is a global phenomenon marked by a significant increase in the elderly population due to rising life expectancies and declining fertility rates. As societies adapt to this demographic shift, one critical issue that emerges is the relocation of older individuals to institutional settings. In this context, gender differences become apparent, with varying proportions of men and women residing in these facilities. This narrative review explores the underlying reasons behind transition to old-age homes and existing gender differences. This narrative review employed a systematic approach to gather relevant literature from PubMed and Google Scholar. Articles were chosen according to their focus on gender disparity and elderly relocation. The review synthesized findings from these sources to identify disparities and reasons. The review revealed that elderly individuals relocate to old-age homes due to reasons such as lack of support from children, death of spouse, loneliness, no caretaker at home, misbehavior of daughter-in-law, children settled abroad, financial issues, service to God, not to be a burden on others, and health issues. However, significant gender differences were also observed. Women, who generally have a longer life expectancy, often experience social isolation and face challenges in maintaining social networks. Understanding the reasons behind elderly relocation to old-age homes is crucial for developing targeted interventions and policies. By addressing the unique challenges faced by the elderly, policymakers and care providers can create more effective solutions to enhance the later life.